2021
DOI: 10.1177/08862605211005139
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Girl-child Marriage and Intimate Partner Violence in Sub-Saharan Africa: Insights From a Multicountry Analysis of Demographic and Health Surveys

Abstract: While considerable attention has been given to the health consequences of child marriage in Sub-Saharan Africa (SSA), limited studies exist on its impact on intimate partner violence (IPV) in the region. We address this gap by examining the link between child marriage and IPV. We tested our study hypothesis using demographic and health survey data of 28,206 young women aged 20-24 years from 16 SSA countries with recent surveys (2015-2019). Binary logistic regression models were used to examine the effect of ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 43 publications
1
23
0
1
Order By: Relevance
“…Studies have shown that child brides have decreased autonomy and bargaining power within their household, as well as limited or no access to household funds [ 5 , 40 , 41 ]. Child brides, compared to their peers married as adults, experience more controlling behaviors from their husband and their husband’s family [ 42 ] and bear a greater risk of experiencing IPV [ 43 , 44 ], which could further exacerbate obstacles accessing health services, as seen in studies related to maternal and child healthcare [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that child brides have decreased autonomy and bargaining power within their household, as well as limited or no access to household funds [ 5 , 40 , 41 ]. Child brides, compared to their peers married as adults, experience more controlling behaviors from their husband and their husband’s family [ 42 ] and bear a greater risk of experiencing IPV [ 43 , 44 ], which could further exacerbate obstacles accessing health services, as seen in studies related to maternal and child healthcare [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…IPV variables were derived from the domestic violence model, which used a modified version of the conflict tactics scale to ask questions [33,34]. The questions used to assess physical, emotional, and sexual violence have been published elsewhere in the literature [35][36][37][38][39]. The response options to each of the questions were "never" "often" "sometimes" and "yes, but not in the last 12 months".…”
Section: Variablesmentioning
confidence: 99%
“…The specific questions used to measure the outcome variables were derived from the modified version of the conflict tactics scale [10,11]. The questions used to assess the outcome variables are available in previous studies [12][13][14]. The responses for each question were "never" "often" "sometimes" and "yes, but not in the last 12 months".…”
Section: Plos Onementioning
confidence: 99%
“…The response options were recoded into "No [those that responded 'never' and yes, but not in the last 12 months']" and "Yes [those who responded as often and sometimes']". The recoding of the response options have been used in previous studies [12][13][14]. Key explanatory variable.…”
Section: Plos Onementioning
confidence: 99%